(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
We look history of methodology, all idea for humans wait on knowledge and this idea from use our forefathers to teach students. And to learn by hart new vocabulary use methodic paradigms to us. They were named no matter how many and diverse their types are, they have their paradigm their paradigm in the development of modern methods as paradigmatic methods of fundamental education, and these methods are used by scientists, educators, and special language teaching centers as the main and general methods of language organization over time.